Functional outcome measures for distal radius fractures: A systematic review - Briony Norton; Benjamin Bugden; Karen PY Liu (SAGE Publishing, 2022)
Objective: This systematic review aimed to identify and describe the utility of functional outcome measures reported in intervention trials between 2010 and 2020, and to map these measures to the International Classification of Functioning, Disability and Health (ICF) model. Method: The search was carried out on MEDLINE, CINAHL and Cochrane Register of Clinical Trials. Peer-reviewed intervention studies detailing the functional outcome measures used for any treatment for distal radius fracture were selected. Participant characteristics, outcome measures reported and the trends in their use over time and geographical locations were extracted. Results: This review analysed 119 studies. Thirty-one functional outcome measures were used across 36 countries. Ninety-two percent of studies measured both the Body Function/Structure and Activity/Participation domains of the ICF. The most frequently used measures were the Disabilities of the Arm, Shoulder and Hand Questionnaire, Range of Motion and Grip Strength. There is a lack of measures on successful return to meaningful occupation. Conclusion: The outcome measures identified were equally spread across the ICF domains. There is a growing importance of Patient-Reported Outcome Measures to supplement performance-based measures, but a lack of measure on successful return to meaningful occupation.